How COVID-19 Triggers Our Herding Behavior? Risk Perception, State Anxiety, and Trust - Lee, Yi-Chih; Wu, Wei-Li; Lee, Chia-Ko (Frontiers in Public Health, 2021)
People have felt afraid during the outbreak of coronavirus disease 2019 (COVID-19), because a virus is an invisible enemy. During the pandemic outbreak, society has become worried about the spread of infections and the shortage of protective equipment. This common fear among the public subsequently deepens each person’s fear, increasing their belief in the content reported by the media and thus actively compelling these individuals to engage in the behavior of panic buying. In this study, we explored the effects of the public’s risk perception, state anxiety, and trust in social media on the herding effect among individuals. The study was based on an online questionnaire survey and convenience sampling. The results showed that the public’s risk perception increased their state anxiety and then deepened their willingness to wait in line for a purchase. In addition, the more people that trust the message delivered by the media, the more actively they will join the queue to buy goods. This study also found that anxiety had a greater impact on the public’s willingness to wait for a purchase than trust in social media. Therefore, the top priority for the government should be to reduce the public’s state anxiety and then reduce the herding effect.